Odpowiedź :
Zadanie
a)
3(x - 5) = -45
3x - 15 = -45 l +15
3x = -30 l :3
x = -10
[tex]b)\\\\\frac{1}{3}x+\frac{1}{6}=1\frac{1}{12}\\\\\frac{1}{3}x+\frac{1}{6}=\frac{13}{12}\ \ \ \mid \cdot12\\\\4x +2=13\ \ \ \mid-2\\\\4x=11\ \ \ \mid:4\\\\x=\frac{11}{4}\\\\x=2\frac{3}{4}\\\\ c)\\\\x-\frac{3x-1}{4}=2x-\frac{x+5}{3}\ \ \ \mid\cdot12\\\\12x-3(3x-1)=24x-4(x+5)\\\\ 12x-9x+3=24x-4x-20\\\\3x+3=20x-20\ \ \ \mid-3\\\\ 3x= 20x-23\ \ \ \mid-20x\\\\-17x=-23\ \ \ \mid:(-17)\\\\x=\frac{23}{17}\\\\x=1\frac{6}{17}[/tex]
Odpowiedź:
a) 3 ( x-5) = - 45
3x -15= - 45
3x= - 45 +15
3x= - 30 /:3
x= - 10
spr... 3* (-10) -15= - 45
- 30 - 15= - 45
-45 = - 45
L=p
b) 1/3 x +1/6 = 1 i 1/12
1/3 x= 1 i 1/12 - 1/6 ( 1 i 1/12 -1/6= 13/12- 2/12= 11/12)
1/3 x= 11/12 /:1/3 (11/12 :1/3= 11/12*3( skracamy 12 i 3 przez 3)=11/4)
x 11/4 = 2 i 3/4
spr... 1/3 *11/4 +1/6= 1 i 1/12
11/12 + 2/12= 1 i 1/12
13/12= 1 i 1/12
1 i 1/12= 1 i 1/12
L=P
c) x-3x -1/4 = 2x -x +5/3
x-3x -2x +x= 5/3 +1/4
-3x= 20/12+3/12
-3x= 23/12 *(-1)
3x= -23/12 = - 1 i 11/12/:3
x= - 23/36
spr... - 23/36 - 3*(-23/36) -1/4= 2*(-23/36) - (-23/36 )+5/3
-23/36 +69/36 -9/36 = -46/36 + 23/36 +60/36
37/36= 37/36
L=P
Szczegółowe wyjaśnienie: